2000
DOI: 10.1523/jneurosci.20-07-02470.2000
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Cannabinoid Inhibition of GABAASynaptic Transmission in the Hippocampus

Abstract: The localization of cannabinoid (CB) receptors to GABAergic interneurons in the hippocampus indicates that CBs may modulate GABAergic function and thereby mediate some of the disruptive effects of marijuana on spatial memory and sensory processing. To investigate the possible mechanisms through which CB receptors may modulate GABAergic neurotransmission in the hippocampus, whole-cell voltage-clamp recordings were performed on CA1 pyramidal neurons in rat brain slices. Stimulus-evoked GABA(A) receptor-mediated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

27
270
3
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 371 publications
(302 citation statements)
references
References 62 publications
(101 reference statements)
27
270
3
2
Order By: Relevance
“…CB1R activation does not seem to affect mIPSCs (Hoffman & Lupica, 2000;Chen et al, 2003, but see later) and, likewise, hippocampal DSI was reported to affect 12 M.A. Diana & A. Marty DSI/DSE: two forms of CB1R-mediated plasticity mIPSCs frequency only minimally (Pitler & Alger, 1994).…”
Section: Hippocampal Dsi Involves the Regulation Of N-type Calcium Chmentioning
confidence: 86%
See 1 more Smart Citation
“…CB1R activation does not seem to affect mIPSCs (Hoffman & Lupica, 2000;Chen et al, 2003, but see later) and, likewise, hippocampal DSI was reported to affect 12 M.A. Diana & A. Marty DSI/DSE: two forms of CB1R-mediated plasticity mIPSCs frequency only minimally (Pitler & Alger, 1994).…”
Section: Hippocampal Dsi Involves the Regulation Of N-type Calcium Chmentioning
confidence: 86%
“…Moreover, DSI spread between pyramidal cells takes place only at short distances (up to 20 mm), indicating that only passive diffusion of cannabinoids, but not a modulation of presynaptic firing, is involved ). Thus, CB1R action on GABAergic interneurons could simply be explained by an inhibition of presynaptic calcium conductances (Hoffman & Lupica, 2000).…”
Section: Hippocampal Dsi Involves the Regulation Of N-type Calcium Chmentioning
confidence: 99%
“…These GABAergic interneurons are believed to orchestrate fast synchronous oscillations in the gamma range, a critical process in synchronizing pyramidal cell activity (Hajos et al, 2000;Hoffman and Lupica, 2000). Gamma oscillations are synchronized over long distances in the brain and are hypothesized to 'bind' together sensory perceptions and to play a role in cognition (reviewed in Wilson and Nicoll, 2002).…”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%
“…Abnormalities in gamma band synchronization have been reported in schizophrenia (Spencer et al, 2003). Activation of these presynaptic CB1Rs reduces GABA release by interneurons (Sullivan, 1999;Katona et al, 1999a), which in turn would disrupt the synchronization of pyramidal cell activity (Wilson and Nicoll, 2002;Hoffman and Lupica, 2000), thereby interfering with associative functions, disrupting normal gating mechanisms, and eventually inducing psychotic symptoms. …”
Section: The Mechanism Of the Psychotic Symptoms Induced By D-9-thcmentioning
confidence: 99%
“…Moreover, cannabinoids were shown to inhibit GABA release by activating these receptors and suppressing GABA A -receptor mediated inhibitory postsynaptic currents in CA1 pyramidal cells. 19,20 However, beside the expression in GABAergic neurons, some electrophysiological experiments also suggested that glutamatergic principal cells may carry presynaptic CB1 receptors, which may explain their interference with long-term potentiation induction. 4,31,38 In contrast, CB1 mRNA was only found in these principal cells at low levels, slightly above the background, or low to moderate levels in the aged human hippocampus.…”
mentioning
confidence: 99%